PROGRAM PEMBERDAYAAN TIM PENGGERAK PKK DESA AMPELDENTO, KARANGPLOSO, MALANG MELALUI KEGIATAN PENGEMBANGAN SISTEM AKUAPONIK - Asus Maizar Suryanto Hertika; Mohamad Fadjar; Setya Widi Ayuning Permanasari; Bimo Aji Nugroho (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
PKK (Family Welfare Empowerment) group in Ampeldento Village is a community group whose role needs to be increased, especially in improving family welfare. The problem they have is that the PKK group does not understand the potential of the narrow land owned by the family is the potential to increase family nutrition through the development of aquaponic cultivation systems. Therefore, carried out the implementation of community service programs through the development of the aquaponics system. Data collection techniques are done through interviews and questionnaires. Evaluation of community understanding of the program was carried out using pre-test and post-test. Based on the results of questionnaires and interviews before the program's implementation, it was found that 70% of respondents did not know aquaponics, 50% were not interested, 35% were hesitant in developing aquaponics independently and 45% doubted aquaponics could improve people's welfare. Results improved significantly after the program's implementation and were inversely proportional, with 95% of the community believing that aquaponics could improve welfare and 70% of respondents wanted to develop it independently. Respondents stated that vegetables produced are faster growing, tasty, green, nutritious and large.